Asymmetric syntheses of moiramide B and andrimid - Davies, S; Dixon, D (1998)
The first highly diastereoselective asymmetric syntheses of moiramide B 2 and andrimid 3 have been achieved using lithium amide (R)-6 and pyrrolidinone auxiliary (R)-9. Pyrrolidinone auxiliary (R)-9 was used to create the novel (S)-3-methyl-N-benzyloxysuccinimide (S)-11 which was subsequently acylated with the highly reactive tert-butoxycarbonyl-protected N-carboxy anhydride of L-valine (Boc-val-NCA) (S)-19 under strongly basic conditions, without racemisation. Lithium amide (R)-6 was used to synthesise homochiral D-β-phenylalanine tert-butyl ester 25.